2021
DOI: 10.3390/microorganisms10010009
|View full text |Cite
|
Sign up to set email alerts
|

The Azurin Coding Gene: Origin and Phylogenetic Distribution

Abstract: Azurin is a bacterial-derived cupredoxin, which is mainly involved in electron transport reactions. Interest in azurin protein has risen in recent years due to its anticancer activity and its possible applications in anticancer therapies. Nevertheless, the attention of the scientific community only focused on the azurin protein found in Pseudomonas aeruginosa (Proteobacteria, Gammaproteobacteria). In this work, we performed the first comprehensive screening of all the bacterial genomes available in online repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Stemming from those premises, in this work we have evaluated the presence of azurin genes in different biological samples (i.e., saliva, stool, and biopsy) from CRC patients and healthy controls, investigating on the possible relationship existing between the disease occurrence and the different microbiota body compartments associated. Moreover, as the presence of azurin genes has been correlated to specific bacterial groups of environmental and gut origin [62], it might help in a future translation to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stemming from those premises, in this work we have evaluated the presence of azurin genes in different biological samples (i.e., saliva, stool, and biopsy) from CRC patients and healthy controls, investigating on the possible relationship existing between the disease occurrence and the different microbiota body compartments associated. Moreover, as the presence of azurin genes has been correlated to specific bacterial groups of environmental and gut origin [62], it might help in a future translation to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As a further step, we analyzed HTS results obtained from previous research [49] in the light of the evidences from Gammuto et al [62], this last specifically evaluating the phylogenetic distribution of azurin gene. These results allowed us to focus on a defined set of taxa known for harbouring azurin genes, rather than the entire community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper, the distribution of the azurin gene—coding for a protein of relevant interest because of its anticancer activity—was evaluated in the three domains of life. The observed patchy distribution of this gene suggested a possible loss of this gene during the evolution of several bacterial phyla and/or an ancient horizontal transfer [ 13 ]. Comparative genome analyses have also been performed to better characterize microorganisms belonging to the bacterial Aminobacter genus [ 14 ], Vibrio parahaemolyticus isolates from seafood [ 15 ], and methanogenic archaea [ 16 ].…”
mentioning
confidence: 99%
“…The understanding of the genetic and ecological processes associated with the different microorganisms and their genomes, and the study of their metabolic potential, can also open new intriguing perspectives for their possible biotechnological use. Indeed, Artuso et al [ 14 ] proposed that Aminobacter species could be exploited in bioaugmentation and bioremediation processes, while Gammuto et al [ 13 ] suggested a possible development of new tools based on the use of P. aeruginosa azurin p28 domain for treating cancer diseases. Finally, in another work comprised in this Special Issue, Choi et al [ 19 ] engineered the yeast Saccharomyces cerevisiae by modifying the expression of three peroxisome proliferation-related proteins: the obtained mutant strains had an increased amount of peroxisomes and/or enlarged peroxisomes that provided additional storage space for the accumulation of protopanaxadiol synthesized through the expression of heterologous biosynthetic genes.…”
mentioning
confidence: 99%